The Effect Of Diabetic Foot Spa On Ankle Brachial Index And Foot Sensitivity Of Diabetes Mellitus Type 2 - Wardani, Erika Martining; Wijayanti, Lono; Ainiyah, Nur (Universitas Respati Yogyakarta, 2019)
Diabetes Mellitus (DM) is a metabolic disorder which marked by the hyperglycemia that appeared because of insulin secretion disorder and/or the increase of cellular insulin resistance. DM patients have a higher risk to experience foot problems due to blood vessels disorders causing the circulation of blood from legs is decreased. Purposed this research is diabetes could be prevented by doing a foot spa diabetic which the activities include foot exercises, warm water cleansing and massage. The method used in this study is Quays Experiment pre-post control group design. The population on this study was patients with Diabetes Mellitus Type 2 in Waru health center. The sample used was 60 people, divided into 2 groups; intervention and control group, with sampling technique of simple random sampling. The data collection was using observation sheets of diabetic foot SPA; the tool used to assess blood glucose levels was glucometer, whereas cotton, brush and needle were used to assess the foot sensitivity. The data was then analyzed with t-test. The result of the study showed that there were effecton the foot sensitivity (t=10,73, p value =0, 000) and there were effectdecrese on ankle brachial index(t=12,34, p value =0, 000). It is important for families and communities to give motivation to the diabetes mellitus patients to do diabetic foot SPA as one of alternative therapies to prevent foot complications such as foot ulcers and even amputation